Hubungan Dukungan Keluarga dan Komunikasi Terapeutik terhadap Tingkat Kecemasan Pasien di Ruang ICU - Nur Anisah; Dwi Retno Sulistyaningsih; Erna Melastuti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
The Intensive Care Unit (ICU) is a specialized unit in a hospital that provides intensive care and close monitoring for critically ill patients. This unit is equipped with advanced medical equipment such as ventilators and hemodynamic monitors, and has a high staffing ratio to ensure optimal care (Smith & Jones, 2020; Brown et al., 2019; Williams & Green, 2021).  The multidisciplinary team in the ICU, including specialist physicians and trained nurses, works together to meet the medical and psychological needs of patients (Taylor, 2022; Miller & Adams, 2018). According to the WHO (2023), 10–20% of hospital patients require ICU care. In Indonesia, ICU patients account for approximately 15% of total hospital patients (Kusuma, 2021). Data from Dr. Moewardi Regional Hospital (RSUD) shows an increasing trend in ICU patients, primarily due to infectious diseases (Ministry of Health, 2021). Meanwhile, in the ICU of Sultan Agung Islamic Hospital (RSI Sultan Agung Semarang), 1,278 patients were admitted between January and October 2024, with the most cases being respiratory failure (143 patients). This study used a quantitative design with a cross-sectional approach. The sample consisted of conscious patients treated in the ICU and met the inclusion criteria, with 71 respondents.  The research instrument used a validated questionnaire to measure family support, therapeutic communication, and anxiety levels. Data analysis was performed using the Spearman test. Based on the Spearman test, the 71 respondents were found to have the following characteristics: the highest age group was early elderly (36.6%), the highest gender was male (64.8%), the highest education level was high school (45.1%), the highest occupation was 80.3%, high family support (74.6%), good therapeutic communication (90.1%), and mild anxiety (59.2%). There is a significant relationship between family support and patient anxiety levels. Furthermore, therapeutic communication also significantly reduced patient anxiety levels in the ICU at Sultan Agung Islamic Hospital, Semarang.